BEHAVIOR OF DOMESTIC PIGS - Gil Dutra Furtado (Environmental Smoke, 2023)
The study of the actions of pigs gives veterinarians the opportunity to know and recognize their behavior, facilitating their preventive and curative care. Pigs have different behaviors, and these animals are very intelligent and have actions and reactions that are very characteristic of their wild descendants, which are wild boars, which helps, in general, in the understanding of these behaviors. This report presents results of observations and records of breeders that, as a whole, help in the study of swine ethology.